Optimalisasi Pengelolaan Arsip Digital: Implementasi Sistem Berbasis Web dengan Metode Waterfall di DPPKP Provinsi Papua Tengah - Gunawan Prayitno; Isa Bryan Imbiri (Jurnal Teknologi dan Informatika, 2026)
The Department of Agriculture, Food, Marine Affairs, and Fisheries (DPPKP) of Central Papua Province faces significant challenges in document archive management that is still performed manually. This research aims to develop a web-based document archive application to improve archiving efficiency and support digital transformation in the government sector. The research methodology uses a software engineering approach with the Waterfall method covering five stages: requirements analysis, system design, implementation, testing, and maintenance. The application was developed using PHP, MySQL, and Bootstrap with main features including document upload/download, category and keyword-based search, and authentication system for data security. Black-box testing results show all system functions operate according to user requirements with 100% success rate. System implementation successfully reduced document search time from an average of 10 minutes to less than 2 minutes, increasing employee work efficiency by 75%. Performance evaluation shows an average response time of 1.2 seconds with 99.7% system availability. This research contributes to government information system development literature and provides practical solutions for archive digitalization in regional government agencies.